Compulsive sexual behavior disorder: rates and clinical correlates in a community sample - Grant, Jon E.; Boutouis, Sophie; Collins, Madison; Chamberlain, Samuel R. (Frontiers in Psychiatry, 2025)
BackgroundThis study sought to examine the rate of compulsive sexual behavior disorder (CSBD) in a sample of adults drawn from the community and its associated mental health correlates.MethodsAn online survey of “Personality, Mental Health, and Well-Being” was distributed via Prolific to 300 adults aged 18 to 75 years. The survey measured a range of behaviors, such as sexual behavior, alcohol and drug use, and dimensional constructs of impulsivity and compulsivity using validated self-report instruments.ResultsA total of 296 participants (54.7% female) completed the survey and were included in the analysis. The overall prevalence of probable compulsive sexual behavior disorder (CSBD) was 10.8% (n=32). Compared to adults without CSBD, those with CSBD were more likely to be younger and identify as bisexual. In addition, they were more likely to have attention-deficit hyperactivity disorder (ADHD) and borderline personality disorder (BPD) symptoms, social media and drug use problems, and higher levels of obsessionality, trans-diagnostic compulsivity, and trans-diagnostic impulsivity. Gender, race, and alcohol use did not significantly differ between groups.ConclusionCSBD appears to be common in adults and is equally represented in males and females. CSBD appears to have obsessive, compulsive, and impulsive traits and this may have nosological importance.